Mercury's low‐degree geoid and topography controlled by insolation‐driven elastic deformation. Issue 18 (25th September 2015) - Tosi, N.; Čadek, O.; Běhounková, M.; Káňová, M.; Plesa, A.‐C.; Grott, M.; Breuer, D.; Padovan, S.; Wieczorek, M. A.
Abstract Mercury experiences an uneven insolation that leads to significant latitudinal and longitudinal variations of its surface temperature. These variations, which are predominantly of spherical harmonic degrees 2 and 4, propagate to depth, imposing a long‐wavelength thermal perturbation throughout the mantle. We computed the accompanying density distribution and used it to calculate the mechanical and gravitational response of a spherical elastic shell overlying a quasi‐hydrostatic mantle. We then compared the resulting geoid and surface deformation at degrees 2 and 4 with Mercury's geoid and topography derived from the MErcury, Surface, Space ENvironment, GEochemistry, and Ranging spacecraft. More than 95% of the data can be accounted for if the thickness of the elastic lithosphere were between 110 and 180 km when the thermal anomaly was imposed. The obtained elastic thickness implies that Mercury became locked into its present 3:2 spin orbit resonance later than about 1 Gyr after planetary formation.